Development of deep learning algorithms for predicting blastocyst formation and quality by time-lapse monitoring - Qiuyue Liao (Nature Portfolio, 2021)
Liao et al. propose a deep learning model to predict blastocyst formation using TLM videos following the first three days of embryogenesis. The authors develop an ensemble prediction model, STEM and STEM+, which were found to exhibit 78.2% and 71.9% accuracy at predicting blastocyst formation and useable blastocysts respectively.